2023
DOI: 10.3390/children10060956
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Physical Literacy-Based Intervention for Increasing Physical Activity Levels and Improving Health Indicators in Overweight and Obese Adolescents (CAPACITES 64)

Abstract: Recently, the concept of Physical Literacy (PL) has emerged as a key concept for promoting active behavior and improving health indicators in adolescents. Overweight and obese adolescents have a low level of Physical Activity (PA), low cardiorespiratory capacity, and high Body Fat percentage (%BF). However, the development of PL in the interest of health improvement has never been studied in overweight and obese adolescents. The objective of this study was to evaluate the impact of an intervention developing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“… 51 Research has shown that PL-based intervention effectively improve health indicators such as cardiorespiratory fitness, overweight and obese on adolescents. 52 In addition, Clutterbuck et al reported the improvements in cognitive-related outcomes through transition-focused sports training program, 53 but another study pointed that school-based physical activity programs did not affect cognitive performance. 54 The research on comprehensive interventions targeting the physical and cognitive development of school-age children is limited.…”
Section: Introductionmentioning
confidence: 99%
“… 51 Research has shown that PL-based intervention effectively improve health indicators such as cardiorespiratory fitness, overweight and obese on adolescents. 52 In addition, Clutterbuck et al reported the improvements in cognitive-related outcomes through transition-focused sports training program, 53 but another study pointed that school-based physical activity programs did not affect cognitive performance. 54 The research on comprehensive interventions targeting the physical and cognitive development of school-age children is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Raising individuals' awareness about the negative consequences of obesity can facilitate health literacy and a greater interest in the issue [22]. In recent years, the accessibility of information from electronic sources, particularly in light of the advancements in internet technology by digitalization, has elevated the signi cance of the e-health literacy concept.…”
Section: Introductionmentioning
confidence: 99%